ANALISIS KONTEKS PELAKSANAAN KEBIJAKAN PENATAAN TRANSPORTASI ANGKUTAN UMUM DI KOTA BANDUNG - Arif Moelia Edie (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2019)
This study aims to analyze the policy context of Local Regulation 16/2012. Data are collected through interviews, observation and documentary study. In term of context of policy, the political will of the government cannot be implemented due to strong patron-client relation among the actors who channelize their economic interest. Good governance and public consultation is not well institutionalized. Many deviances are committed by the program implementers. Responsiveness of bureaucracy and local parliament is still low, thus not sufficiently contribute to the policy implementation. Keywords: Policy Implementation, Public Transportation Arrangement